The fungal microbiome in chronic rhinosinusitis: richness, diversity, postoperative changes and patient outcomes. Issue 4 (5th February 2014) - Cleland, Edward John; Bassioni, Ahmed; Boase, Samuel; Dowd, Scot; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Our understanding of fungi in chronic rhinosinusitis (CRS) has been limited by previously employed detection techniques. This study examines the fungal component of the microbiome in CRS patients and controls using a highly sensitive culture‐independent molecular technique. The aims of this study include the characterization of fungal richness, prevalence, abundance, temporal changes, and their relationship with patient outcomes. Methods Swabs were collected from the sinuses of 23 CRS patients and 11 controls. Collection occurred intraoperatively, and at 6 and 12 weeks postoperatively. DNA was extracted from the swabs and fungal outcomes were determined through 18S ribosomal DNA (rDNA) fungal tag‐encoded FLX amplicon pyrosequencing. Results Fungi were ubiquitous to all patients. A total of 207 fungal genera were detected, with a mean sample richness of 8.18 and 12.14 in the control and CRS groups, respectively. Malassezia was detected in all patients at surgery and was also the most abundant. Postoperatively, fungal richness decreased (p < 0.05) and was associated with declines in the prevalence of Fusarium and Neocosmospora (p < 0.05). Neocosmospora was also less abundant postoperatively (p < 0.05). No correlations were found with quality of life. Conclusion This is the first study to use a highly sensitive pyrosequencing technique to reveal the true diversity of fungi in the sinuses of CRS patients and postoperative changes in richness. The presence of Malassezia, a genus not previously described in the sinuses, is of great interest, and its potential as a disease modifier should see further investigation given its association with atopic disease.